2015
DOI: 10.1002/mc.22436
|View full text |Cite
|
Sign up to set email alerts
|

The role of base excision repair in pathogenesis of breast cancer in the Polish population

Abstract: Breast cancer (BC) is leading type of cancer among group of women, which determines almost 23% of invasive cancers. It has been reported repeatedly that the level of oxidative stress is higher for BC in comparison to cancer-free woman. The goal of the present study was to evaluate the role of base excision repair (BER) pathway in the development of BC. One-hundred seventy-one women with confirmed BC and 222 healthy controls were enrolled in presented study. The level of oxidative DNA damage and the kinetic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, there is still an elevating mortality in some particular countries [ 4 ]. It has been demonstrated that both environmental and genetic factors contribute to the risk of BC [ 5 ]. In addition, several clinicopathological parameters have been introduced in BC management, including clinical stages, histological grade, histological type and lymph node metastasis (LNM).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still an elevating mortality in some particular countries [ 4 ]. It has been demonstrated that both environmental and genetic factors contribute to the risk of BC [ 5 ]. In addition, several clinicopathological parameters have been introduced in BC management, including clinical stages, histological grade, histological type and lymph node metastasis (LNM).…”
Section: Introductionmentioning
confidence: 99%
“…This method of repair involves the removal of damaged bases form the double helix and the excision of the damaged section from the DNA structure [19]. Single nucleotide polymorphisms (SNPs) in members of the base excision repair pathway, XRCC1 and APE1, have been reported as contributing to increased risk of breast cancer, although population studies have not yielded consistent results [20, 21].…”
Section: Dna Damage Repair Pathwaysmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the XRCC1 and APE1 base excision repair (BER) genes have also been reported to increase the risk of breast cancer on the level of individuals. However, no population specific data was reported [19,20]. Nucleotide excision repair (NER) deficiency has also been associated with early stage breast cancer.…”
Section: Introductionmentioning
confidence: 99%